Synthesis of Anti-Fungals, from Chiral imidazolyl-imino and amino Compounds - Khlifa, Mousa; Zaed, A. M (Journal of natural sciences, life and applied sciences, 2017)
This work describes the synthesis of novel nonracemic derivatives of imidazole. Some oxidation reactions using Mn(II), Se(II) and nitric acid were employed for the synthesis of the starting materials, imidazolyl carboxaldehydes in straightforward steps. These key step compounds were then subjected to schiff bases and reductive amination processes for the synthesis imidazolylimio and imidazolylamino compounds using standard conditions. Attempts to purify some imidazolylamino compounds using kugelrohr distillation technique have been unsuccessful. However, recrystallization from acetonitrile allowed isolation some compounds in good yields. The new compounds that were synthesised were potential ligands for complexation of metals. Ag(I) was used to synthesis of several metal complexes. These compounds were characterised by nuclear magnetic resonance (NMR) and fourier transform infrared spectroscopy (FTIR) as well as elemental analysis method. These imidazole derivatives have been screened for activity against Candida albicans. Although the S-enantiomer of N-[(1E)-1-benzyl imidazol-2-ylmethylene]-N′-(1-phenylethyl)amine was found inactive against C. albicans, the R-enantiomer showed moderate activity. However, in two instances the activity was greater than that for ketoconazole which is a common agent to cure candida infestation.